1954
DOI: 10.1121/1.1907411
|View full text |Cite
|
Sign up to set email alerts
|

Time Factors in Relative and Absolute Pitch Determination

Abstract: Error measures of pitch discrimination were obtained as a function of the time lapse between standard and comparison tones. The time interval ranged from one second to one week, establishing a “curve of forgetting.” Half of the subjects possessed absolute pitch. Results indicate that for short time intervals there is no observable difference in pitch discrimination between the two groups of subjects. With longer intervals there is a decided discrepancy, so long as the tone is within the musical range. This dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0
1

Year Published

1973
1973
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 0 publications
1
61
0
1
Order By: Relevance
“…Newman-Keuls post hoc tests revealed that in overall error rates, the 300-msec and I-sec intervals were not significantly different, nor were the 3-sec and 5-sec conditions (p> .05), but both the 3·sec and 5-sec conditions had significantly more errors than the 300-msec and I-sec conditions (p < .05). It is tempting to relate the greater errors in the longer intervals to previous fmdings of a decline in pitch recognition over longer silent retention intervals (Harris, 1952;Bachem, 1954). However, the interaction between temporal interval and intervening tone condition suggests a very different interpretation of the temporal interval main effect (see Figure 2).…”
Section: Intervening Conditionmentioning
confidence: 99%
“…Newman-Keuls post hoc tests revealed that in overall error rates, the 300-msec and I-sec intervals were not significantly different, nor were the 3-sec and 5-sec conditions (p> .05), but both the 3·sec and 5-sec conditions had significantly more errors than the 300-msec and I-sec conditions (p < .05). It is tempting to relate the greater errors in the longer intervals to previous fmdings of a decline in pitch recognition over longer silent retention intervals (Harris, 1952;Bachem, 1954). However, the interaction between temporal interval and intervening tone condition suggests a very different interpretation of the temporal interval main effect (see Figure 2).…”
Section: Intervening Conditionmentioning
confidence: 99%
“…Generally, people tend to think that absolute pitch possessors are superior in all of their auditory abilities. However, in the field of auditory and music psychology, researchers have focused on the etiology of absolute pitch [1][2][3][4][5][6][7] or the merits and demerits of absolute pitch in music cognition [8][9][10][11][12], but have not closely studied the basic hearing abilities of absolute-pitch possessors for general sounds outside the context of music. Studying the basic hearing abilities of absolute pitch possessors may bring insights not only into the mechanisms of absolute pitch itself, but also into problems such as individual differences and the plasticity of auditory functions.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, superior discrimination does not imply better learning and memory abilities. For example, while long-term retention of pitch is surprisingly accurate only in absolute pitch (AP) possessors (Bachem, 1954), AP listeners do not have superior auditory acuity compared to non-AP musician listeners (e.g., Fujisaki & Kashino, 2002;Levitin & Rogers, 2005). Here, we focus on the general ability of a listener to exploit acoustical information, without investigating the differential role of discrimination, memory and learning abilities.…”
mentioning
confidence: 99%